THE STRATEGY OF NORTH SUMATRA PROVINCE BAWASLU IN PREVENTING VIOLATIONS OF ELECTION IN 2019 THROUGH SOCIAL MEDIA - rifa fachry; Farah DIba; Gunawan 2006; Nur Fadhil Muhammad; annisa khairuna; Fiki Alan Nuriansyah (UIN Mataram, 2021)
In the 2019 political year, social media has a very strategic role. In addition, the frequency of the emergence of hate speech and hoax news are even higher in the 2019 Election. Bawaslu as a supervisory institution has an important role to provide education to prevent election violations. So, in this study, researchers want to find out how the role and strategy of the Election Supervisory Body (Bawaslu) of North Sumatera Province prevent violations in the 2019 Election via social media. The formulation of the problem in this study is as follows: (1) What is the strategy of the North Sumatera Province Bawaslu in an effort to prevent violations of the 2019 Election via social media, (2) What is the role of the North Sumatera Province Bawaslu in an effort to prevent violations of the 2019 Election via social media. The purpose of this study is to find out and understand what the strategy and role of the Bawaslu of North Sumatera Province in an effort to prevent violations of the 2019 General Election via social media. In this study, data processing and presentation is carried out using qualitative analysis techniques with research procedures that are to explain, manage, describe and interpret research results as a feature, character, or description of certain conditions, or phenomena as answers to the problems studied. Data collection techniques are in the form of observation, interviews, and documentation. This research uses democratic election theory, supervisory theory and institutionalism approach.